2019
DOI: 10.1080/17434440.2019.1626232
|View full text |Cite
|
Sign up to set email alerts
|

Dural sealants for the management of cerebrospinal fluid leakage after intradural surgery: current status and future perspectives

Abstract: Introduction: Cerebrospinal fluid leakage is a complication after intradural surgery and is associated with severe secondary complications like compromised wound healing and meningitis. Dural sealants are meant to augment the primary dural closure in order to achieve a watertight closure. Areas covered: This review summarizes the efficacy of currently available dural sealants. Potential future improvements and biomaterials are discussed. Expert opinion: The use of a dural sealant seems to be the logical method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 36 publications
0
21
0
2
Order By: Relevance
“…Systematic reviews have shown that CSF leakage still occurs after intradural surgery and that the CSF leakage rate does not decrease with sealant use. However, sealants are assumed to be an important adjunct to create a watertight closure of the dura [33]. Although CSF leakage will most likely never be eliminated in clinical practice, if a durable watertight closure could be achieved, a reduction in the CSF leakage rate would certainly be expected.…”
Section: Discussionmentioning
confidence: 99%
“…Systematic reviews have shown that CSF leakage still occurs after intradural surgery and that the CSF leakage rate does not decrease with sealant use. However, sealants are assumed to be an important adjunct to create a watertight closure of the dura [33]. Although CSF leakage will most likely never be eliminated in clinical practice, if a durable watertight closure could be achieved, a reduction in the CSF leakage rate would certainly be expected.…”
Section: Discussionmentioning
confidence: 99%
“…[48] This concern about volume swelling is severe in spinal surgery for the confined operation space and delicate neural tissue. [40,49] DuraSeal for dural repair with a swelling ratio higher than 50% has been reported with the complications in inducing spinal cord compression in some cases. [18,19,50,51] Then, a low-swelling formulation (swelling ratio of 19%) was developed, but it was not suggested for use in very confined spaces.…”
Section: Avoiding Compression Injury To the Spinal Cord Using Raas Hy...mentioning
confidence: 99%
“…24,25 Although robust and stable seals of the dura mater are critical for post-neurological surgery, according to systematic reviews and in vitro studies, the currently available dural sealants still lack efficacy. 26,27 Van Doormaal et al reported a comparison analysis of nine common dural sealants using an in vitro model. With a modified ASTM F2392-04 (Standard Test Method for Burst Strength of Surgical Sealants) test methodology, their study quantified the acute burst pressure and a 3-day sustained pressure (16 mmHg) test of a dural repair using an animal model.…”
Section: Endoscopic Endonasal Transsphenoidal Surgery and Complicationsmentioning
confidence: 99%